Motives for alcohol use, risky drinking patterns and harm reduction practices among people who experience homelessness and alcohol dependence in Montreal - Rossio Motta-Ochoa; Natalia Incio-Serra; Alexandre Brulotte; Jorge Flores-Aranda (BMC, 2023)
Abstract Background People experiencing homelessness are disproportionately affected by harms related to alcohol use. Indeed, their alcohol dependence is associated with numerous physical and mental health problems along with strikingly high rates of alcohol-related mortality. Recent research has extensively examined alcohol use patterns among people experiencing homelessness in an effort to develop interventions and treatments for this problem. However, only a few studies have incorporated the perspectives of the individuals under study about their drinking or examined the ways in which they manage the associated harms. To bridge this gap, we conducted a qualitative study exploring the relation between the drinking motives, risky drinking patterns and harm reduction practices of a group of people (n = 34) experiencing homelessness in Montreal, Canada. Methods The qualitative methods we used consisted of semi-structured interviews (n = 12) and focus groups (n = 2, with a total of 22 participants). The content of the collected data was then analyzed. Results Participants identified their various motives for alcohol use (coping with painful memories, dealing with harsh living conditions, socializing/seeking a sense of belonging, enjoying themselves/having fun); their risky drinking patterns (binge drinking, mixing alcohol with drugs, non-beverage alcohol drinking, failing to keep sufficient alcohol on hand to prevent acute withdrawal, drinking in public settings); their harm reduction practices (planning how much to drink, keeping a supply of alcohol to prevent acute withdrawal, hiding to drink, concealing alcohol, drinking alone, drinking/hanging out with others, drinking non-beverage alcohol, and taking benzodiazepines, cocaine or other stimulant drugs); and the rationales underpinning their alcohol use and harm reduction practices. Conclusion Associating the drinking motives of a group of study participants with their risky drinking patterns and harm reduction practices shed light on their rationales for alcohol use, yielding insights that could be used to better tailor policies and interventions to their needs.